DNA polymorphisms at the BCL11A, HBS1L-MYB, and beta-globin loci associate with fetal hemoglobin levels and pain crises in sickle cell disease - Lettre, Guillaume; Sankaran, Vijay G; Bezerra, Marcos André C; Araújo, Aderson S; Uda, Manuela; Sanna, Serena; Cao, Antonio; Schlessinger, David; Costa, Fernando F; Hirschhorn, Joel N; Orkin, Stuart H (Proceedings of the National Academy of Sciences - PNAS, 2008)
Sickle cell disease (SCD) is a debilitating monogenic blood disorder with a highly variable phenotype characterized by severe pain crises, acute clinical events, and early mortality. Interindividual variation in fetal hemoglobin (HbF) expression is a known and potentially heritable modifier of SCD severity. High HbF levels are correlated with reduced morbidity and mortality. Common single nucleotide polymorphisms (SNPs) at the BCL11A and HBS1L-MYB loci have been implicated previously in HbF level variation in nonanemic European populations. We recently demonstrated an association between a BCL11A SNP and HbF levels in one SCD cohort [Uda M, et al. (2008) Proc Natl Acad Sci USA 105:1620-1625]. Here, we genotyped additional BCL11A SNPs, HBS1L-MYB SNPs, and an SNP upstream of (G)gamma-globin (HBG2; the XmnI polymorphism), in two independent SCD cohorts: the African American Cooperative Study of Sickle Cell Disease (CSSCD) and an SCD cohort from Brazil. We studied the effect of these SNPs on HbF levels and on a measure of SCD-related morbidity (pain crisis rate). We strongly replicated the association between these SNPs and HbF level variation (in the CSSCD, P values range from 0.04 to 2 x 10(-42)). Together, common SNPs at the BCL11A, HBS1L-MYB, and beta-globin (HBB) loci account for >20% of the variation in HbF levels in SCD patients. We also have shown that HbF-associated SNPs associate with pain crisis rate in SCD patients. These results provide a clear example of inherited common sequence variants modifying the severity of a monogenic disease.